Mentoring and Schooling Decisions: Causal Evidence - Armin Falk; Fabian Kosse; Pia Pinger (Institute of Labor Economics (IZA), 2020)
Inequality of opportunity strikes when two children with the same academic performance are sent to different quality schools because their parents differ in socio-economic status. Based on a novel dataset for Germany, we demonstrate that children are significantly less likely to enter the academic track if they come from low socio-economic status (SES) families, even after conditioning on prior measures of school performance. We then provide causal evidence that a low-intensity mentoring program can improve long-run education outcomes of low SES children and reduce inequality of opportunity. Low SES children, who were randomly assigned to a mentor for one year are 20 percent more likely to enter a high track program. The mentoring relationship affects both parents and children and has positive long-term implications for children's educational trajectories.
Keywords: C90; I24; J24; J62; 330; mentoring; childhood intervention programs; education; human capital investments; inequality of opportunity; socio-economic status